The Failure of All Mothers or the Mother of All Failures? Juror Perceptions of Failure to Protect Laws - Stanziani, Marissa (Journal of interpersonal violence, 2021)
Failure to protect laws have been an area of interest among legal scholars, child and domestic violence advocates, and the social work and psychology fields with varying focuses on the societal underpinnings of the laws and their application. Despite the pervasive legal literature on “mother blaming” and the revictimization of battered women that these laws engender, few studies have empirically examined if “mother blaming” occurs in these cases, or if battered women are treated more harshly. The aim of the present study was to investigate the impact of defendant sex and presence of domestic violence on mock juror decision making in a failure to protect case. The influences of juror sex on decision making were also examined. Jury eligible community members read a summary of a case in which the defendant was charged with failing to protect their child from a third-party abuser. The sex of the defendant and the presence of domestic violence were manipulated. Participants then rendered a verdict, provided sentencing recommendations, and responded to attitudinal questions about the defendant and perpetrator. Mock jurors were more likely to find the defendant guilty and view the defendant more negatively when the defendant had been the victim of domestic violence. Defendant sex did not affect outcome measures; however, female jurors were more punitive than male jurors. Results are discussed in terms of “victim blaming” and labeling theory of intimate partner violence.